Peningkatan Keamanan dan Kenyamanan Kehidupan Malam Hari dengan Lampu Penerangan Jalan Desa Tak Terjangkau Listrik PT. PLN Desa Belabori Kecamatan Parangloe Gowa - Yustinus Upa Sombolayuk; Syafaruddin -; Zaenab Muslimin; Fitriyanti Mayasari; Yusri Syam Akil; Intan Sari Areni; Hasniaty A; Sri Mawar Said; Ikhlas Kitta; Indar Chaerah Gunadin; Tajuddin Waris (Faculty of Engineering UNHAS, 2021)
Street Lightning is a part of complimentary stucture of street, which can be put at any part of the street. It aims to light the street and its environment. The advanced improvement of street lightning has applied lightning system with solar photovoltaic that has energy efficiency and environmental friendly. Belabori Village in Gowa District uses electricity for residential lighting and has limited street lightning. This condition leads to safety and convenience issues to its society, which can cause decresing in productivity. Therefore, this community service activity is held to give recommendation to Belabory’ society to applied science and technology to attain reachable appropriate energy resources for their needs. This activity established solar photovoltaic based street lightning system that will give safety and comfort to the society during night time and also gave advising about the importance of street lighting for the productivity and how to maintain the facility. To evaluate the usefulness of this activity, method has been applied by comparing the result pre-and-post activity through discussion and survey. The results show that there is an increasing awareness of the importance of the street lightning for safety, convenience and productivity of the society. There is also counsciousness of the Belabori’ society to retain the sustianability of the facility. They are also starting to know some of renewable energy based technologies to increase their productivity.